Many-years changes of yield and «yield waves» in Poltava region - Писаренко, П. В.; Хлебнікова, Я. О. (Scientific Progress & Innovations, 2015)
The paper deals with research of many-years changes of crop yield in Poltava region. Analysis of crop yield changes is carried out at the research period from 1966 to 2012 including. Average graph curves of crop yield are presented. Three periods of crop yield changes with two evident minimum of yield are found out. Average period of «yield wave» for all of crops is given. The role of geliogeophysical factors and moon-earth influences in formation and changes of crop yield is also analyzed.